Rama deco armchair / Mohamad Ihsan Ilias - Ilias, Mohamad Ihsan (Universiti Teknologi MARA, Kedah, 2025)
“Rama Deco: Malay Tiger Butterfly meets Art Deco armchair, exclusively for your residence” This final year project aims to conceptualize the use of nature inspiration in furniture design, which is Malay Tiger Butterfly. This was done with the influence of Art Deco movement which resulted in a unique luxury piece, standing out harmoniously in your living room. With this goal in mind, this project utilised the multiple forms and attributes of the Malay Tiger Butterfly, showcasing the beauty of it in the form of a daily life seater. The “Rama Deco” is not only designed for comfort, but also for its striking visual, which makes it a great conversation starter. The overall combination results in a unique and experimental piece. ”Rama Deco” is not trying to be just an armchair: but the armchair for your living room. This armchair is not only comfy, but also visually unique, with the addition of its rich backstory of Malay Tiger Butterfly, making it a statement for your property. This project invites you to immerse yourself with the presence of “Rama Deco”, bringing your space to a higher level.